Transculturation and contemporary artistic collaboration: pushing the boundaries of histories, epistemologies, and ethics : introduction - Koch, Franziska (The journal of transcultural studies, 2021)
This contribution introduces the themed issue "How we work together: ethics, histories, and epistemologies of artistic collaboration," and summarises the articles that appear within.